Analisis Frasa Idiomatik dalam Lagu “Remaja” pada Album Kereta Kencan Oleh Hivi!: Kajian Fraseologi - Sajida, Yasminee Adzka; -, Haryadi (Bahasa Indonesia Prima, 2024)
This study examines idiomatic phrases in the lyrics of the song “Remaja” from the album “Kereta Kencan” by Hivi! as a form of linguistic expression that reflects the richness of language and culture. This study aims to identify and analyze the idiomatic phrases contained in the song lyrics and explore the meaning and function of these phrases in the context of the lyrics. This study uses a qualitative descriptive methodological approach and the theoretical approach of phraseology. The research data were taken from the lyrics of the song “Remaja” through the techniques of simak-catat and simak bebas libat cakap (SBLC). Data analysis used agih method with direct element division technique (BUL) and lesap technique. The results showed that idiomatic phrases in the song “Remaja” lyrics have deep figurative meanings and function to convey messages and create solid artistic nuances. The findings are expected to provide insight into the dynamics of language in the context of popular culture and its contribution to the development of modern Indonesian, as well as a reference for language researchers and teachers in understanding and teaching the use of idiomatic phrases.